STUDENT PERCEPTIONS OF JIGSAW LEARNING MODEL AT THE SUBJECT OF EDUCATIONAL PROFESSION AT UMMY SOLOK (Universitas PGRI Sumatera Barat, 2018)
The quality of education requires the attention of all parties, especially the government and education personnel. The quality of education will be achieved if all components of education make a change to a better direction. The subject of the educational profession is prepares the students to understand the basics of education as a profession. Many students are not really understand with the subject matter of the educational profession whereas this subject is a very important as a preparation to become a teacher. Therefore lecturers must be able to apply various models that can improve students' understanding. One of them is the jigsaw learning model. This study aims to determine the perceptions of students using jigsaw learning model on the educational profession at UMMY Solok. This research is a descriptive research which is included in survey type. Population in this research which is all student of Economics fifth semester of academic year 2015/2016 which amounted to 15 people who have followed the process educational profession recovery using jigsaw learning model. The sample is a student of Economics fifth semester of academic year 2015/2016, amounting to 15 people in the economic education program FKIP UMMY Solok who have followed subject of educational profession using jigsaw learning model. The sampling technique uses total sampling. Data collection technique using closed questionnaire with rating scale form. The conclusion of this research is student perception by using jigsaw learning model on the subject of the educational profession is very good. Keywords: Perception, Jigsaw Learning Model, The subject of Educational Profession.